Anatomical-physiological characteristics of the selection of young rowers in kaying and canoeing to beginning specialty groups - Savriddin qizi, A. S.; Fatullobekovich, U. F. (Web of Synergy: International Interdisciplinary Research Journal, 2023)
The limit of human capabilities in sports is determined not only by the optimal shape and structure of the body, but also by the structure of human mental activity. The fitness and nature of the athlete is probably more important than his body shape.